LYG1 Deficiency Attenuates the Severity of Acute Graft-Versus-Host Disease via Skewing Allogeneic T Cells Polarization Towards Treg Cells - Liu, Huihui; Yu, Zhengyu; Tang, Bo; Miao, Shengchao; Qin, Chenchen; Li, Yuan; Liang, Zeyin; Shi, Yongjin; Zhang, Yang; Wang, Qingya; Yan, Miao; Song, Zhengyang; et al. (Frontiers in Immunology, 2021)
Acute graft-versus-host disease (aGVHD) is a lethal complication after allogeneic hematopoietic stem cell transplantation. The mechanism involves the recognition of host antigens by donor-derived T cells which induces augmented response of alloreactive T cells. In this study, we characterized the role of a previously identified novel classical secretory protein with antitumor function-LYG1 (Lysozyme G-like 1), in aGVHD. LYG1 deficiency reduced the activation of CD4+ T cells and Th1 ratio, but increased Treg ratio in vitro by MLR assay. By using major MHC mismatched aGVHD model, LYG1 deficiency in donor T cells or CD4+ T cells attenuated aGVHD severity, inhibited CD4+ T cells activation and IFN-γ expression, promoted FoxP3 expression, suppressed CXCL9 and CXCL10 expression, restrained allogeneic CD4+ T cells infiltrating in target organs. The function of LYG1 in aGVHD was also confirmed using haploidentical transplant model. Furthermore, administration of recombinant human LYG1 protein intraperitoneally aggravated aGVHD by promoting IFN-γ production and inhibiting FoxP3 expression. The effect of rhLYG1 could partially be abrogated with the absence of IFN-γ. Furthermore, LYG1 deficiency in donor T cells preserved graft-versus-tumor response. In summary, our results indicate LYG1 regulates aGVHD by the alloreactivity of CD4+ T cells and the balance of Th1 and Treg differentiation of allogeneic CD4+ T cells, targeting LYG1 maybe a novel therapeutic strategy for preventing aGVHD.